2020
DOI: 10.1177/2192568219884913
|View full text |Cite
|
Sign up to set email alerts
|

The Endoscopic Approach to Lumbar Discectomy, Fusion, and Enhanced Recovery: A Review

Abstract: Study Design: Review. Objectives: To review the current state of endoscopic spine surgery with regard to discectomy, interbody fusion, and combination with Enhanced Recovery After Surgery programs in order to evaluate its relevance to the future of spine care. Methods: A review of the literature and expert opinion is used to accomplish the objectives. Results: The greatest strength of endoscopic spine surgery lies in its adherence to the basic tenets of minimally invasive surgery and its innate compatibility w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Endoscopic spine operations leave a smaller surgical footprint than the minimally invasive surgeries they build upon and further the advantages of MIS, including reduced tissue disruption, decreased intraoperative blood loss, and shorter hospital admissions [ 5 ]. Moreover, endoscopic surgeries represent a unique contribution in that they may be performed under conscious sedation instead of general anesthesia [ 6 , 7 ], engendering potential improvement in patient satisfaction [ 8 , 9 ]. In the next review article, the authors will discuss the different approaches to LIF and how innovation in endoscopic techniques has driven the learning requirements for these techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic spine operations leave a smaller surgical footprint than the minimally invasive surgeries they build upon and further the advantages of MIS, including reduced tissue disruption, decreased intraoperative blood loss, and shorter hospital admissions [ 5 ]. Moreover, endoscopic surgeries represent a unique contribution in that they may be performed under conscious sedation instead of general anesthesia [ 6 , 7 ], engendering potential improvement in patient satisfaction [ 8 , 9 ]. In the next review article, the authors will discuss the different approaches to LIF and how innovation in endoscopic techniques has driven the learning requirements for these techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In the last quarter of the 20 th century and early 21 st century, there has been an evident shift from traditional open to minimal invasive spinal surgical techniques (MIS). Endoscopic Spine surgeries (ESS) are also a spectrum of this MIS [1][2][3][4] . In the last ten years, there has been an exponential increase in ESS practice.…”
Section: Introductionmentioning
confidence: 99%
“…In the last ten years, there has been an exponential increase in ESS practice. It is evolving from individual spine surgeons practice to institutional practice and is getting better incorporated 1,3,[5][6][7] . Now even universities and spine societies are incorporating spine endoscopy in their curriculum and guidelines exemplified by North American Spine Society (NASS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although technically more demanding, interlaminar full-endoscopic discectomy has signi cantly reduced surgical invasiveness, thereby expanding the indications for endoscopic surgery [5,[8][9][10]. Speci cally, interlaminar full-endoscopic discectomy offers several advantages over conventional microscopic discectomy, including a smaller skin incision, and thus, less scarring as well as less muscle damage, a lower infection rate and volume of blood loss, a less painful recovery, and a shorter hospital stay [3,[11][12][13][14][15][16][17]. Previous studies have reported that there are no differences in clinical outcomes between interlaminar endoscopic and microscopic discectomy [18][19][20][21][22].…”
mentioning
confidence: 99%